Terruco de m… Insulto y estigma en la guerra sucia peruana - Aguirre, Carlos (2011)
This article explores the short but intense history of the word terruco, a colloquial term which is used as a substitute for terrorist. In particular, the article aims to show that the use of terruco as an insult, although originally aimed at members of groups in arms, contributed decisively during the years of the dirty war and even in recent times, to stigmatize sectors of the Peruvian population, including defenders of human rights, relatives of those detained and other victims of political violence, and in general persons of Indian origin. Its frequent use in torture sessions and episodes of sexual assault added an additional dimension to the connection between the term terruco and generalized forms of abuse and violence which were considered by many Peruvians as necessary and even legitimate during the years of internal armed conflict.